Abducens nerve palsy due to inferior petrosal sinus thrombosis. (June 2017) - Mittal, Shivam Om; Siddiqui, Junaid; Katirji, Bashar
Highlights: Abducens nerve palsy is the most common reason for oculomotor cranial palsy. Abducens nerve and inferior petrosal sinus travels closely in the Dorello's canal. Thrombosis of the inferior petrosal sinus should be on the differential for ipsilateral abducens nerve palsy. Abstract: Isolated unilateral abducens nerve palsy is usually due to ischemia, trauma or neoplasm. Dorello's canal is the space between the petrous apex and superolateral portion of the clivus, bound superiorly by Gruber's ligament. The abducens nerve travels with inferior petrosal sinus (IPS) though the Dorello's canal before entering the cavernous sinus. A 31-year-old man presented with neck pain, and binocular horizontal diplopia, worse looking towards left and at distance. He had a history of intravenous drug abuse but no history of hypertension or diabetes. On examination, he had complete left 6th nerve palsy with normal fundi, pupils, and other cranial nerves. Methicillin-resistant Staphylococcus aureus bacteremia was detected with naïve tricuspid valve endocarditis and multiple septic emboli to lungs with infarcts. His cerebrospinal fluid was normal. MRI of the brain was normal. MRV of head and neck showed thrombosis of the left internal jugular vein, left sigmoid sinus and left inferior petrosal sinus with normal cavernous sinus and no evidence of mastoiditis. He was treated with broad spectrum antibiotics. He was not anticoagulated for fear of pulmonary hemorrhage from pulmonary infarcts. Although cerebral venous sinus thrombosis commonly presents with elevated intracranial pressure, isolated ipsilateral 6th nerve palsy from its compression in Dorello's canal due to thrombosis of the ipsilateral inferior petrosal sinus is extremely rare. To our knowledge, only two patients have been reported with isolated abducens palsy due to IPS thrombosis; one caused by septic emboli and the other developed it during IPS cortisol level sampling.